Charles Sanders Peirce's Semiotic Analysis in Erika Johansen's Novel "The Queen of The Tearling" - Nasution, Zuraidah; Rosliani, Rosliani; Erwany, Lela (Journal of Education, Humaniora and Social Sciences (JEHSS), 2025)
This study explores how Erika Johansen’s novel The Queen of The Tearling (2014) conveys hidden meanings through a semiotic approach. Using a descriptive qualitative method, this study applies Charles Sanders Peirce’s theory—which includes icons, indices, and symbols—to understand how various signs in the novel form deeper messages. This analysis finds that Kelsea Glyn is not just a main character, but also symbolizes resistance against injustice. Her journey reflects the struggle of a young leader in facing tough challenges, while the Tearling Kingdom depicts an oppressed world, full of inequality and social conflict. The sapphire that Kelsea inherits is not only a magical artifact, but also a symbol of wisdom and the great responsibility she must bear. More than just story elements, these signs form a sharp social critique of power and injustice. Using a semiotic approach, this study reveals how the novel speaks to readers about courage, sacrifice, and the struggle for change, showing that its meaning is much deeper than it appears on the surface.